The Value of Character Education in the Series "I'm the Best Muslim" - Hasna Ramadhanti Hidayat; Muhammad Bahagia Ramdami; Penti Septiani; Muhamad Parhan (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: Character Education Value in "I'm The Best Muslim" Series. The value of character education is currently a very important concern for everyone, especially as a Muslim is certainly required to have good character. This research aims to explore the concept of character education through Muslim animation, namely I'm the Best Muslim Season 1. The method used is content analysis. The object of this research, namely the value of character education contained in the series I'm The Best Muslim season 1. The results revealed that the film series I'm The Best Muslim season 1 contains 3 elements of character education values listed in the Pancasila student profile. The three elements are noble character, mutual cooperation, and global diversity. From the three elements of character education values in I'm The Best Muslim season 1 animation, it is an educational show that teaches or can improve the good character of a child and teenager who in the future will become a person with character. The conclusion of the research reveals that strengthening character is very important for children because laying the foundation of character is what can lead children to grow well in the future, through I'm The Best Muslim Season 1 has great potential to be an important means of shaping character and conveying moral messages to the younger generation. Abstrak: Nilai Pendidikan Karakter dalam Series “I’m The Best Muslim”. Nilai pendidikan karakter saat ini menjadi perhatian yang sangat penting dimiliki oleh setiap orang, apalagi sebagai seorang Muslim tentu diharuskan memiliki karakter yang baik. Penelitian ini bertujuan untuk menjelajahi konsep pendidikan karakter melalui animasi Muslim, yaitu I’m the Best Muslim Season 1. Metode yang digunakan ialah analisis konten. Objek penelitian ini, yaitu nilai pendidikan karakter yang terkandung dalam series I’m The Best Muslim season 1. Hasil penelitian mengungkap bahwa film series I’m The Best Muslim season 1 memuat 3 elemen nilai pendidikan karakter yang tercantum pada profil pelajar Pancasila. Ketiga elemen tersebut, yaitu berakhlak mulia, gotong royong, dan berkebinekaan global. Dari ketiga elemen nilai pendidikan karakter yang ada dalam animasi I’m The Best Muslim season 1, merupakan sebuah tayangan mendidik dimana mengajarkan atau dapat meningkatkan karakter baik seorang anak dan remaja yang kedepannya nanti orang tersebut menjadi pribadi yang berkarakter. Kesimpulan penelitian mengungkap bahwa penguatan karakter sangat penting bagi anak karena peletakan pondasi karakter inilah yang dapat menuntun anak untuk tumbuh dengan baik di masa depan, melalui I’m The Best Muslim Season 1 memiliki potensi besar untuk menjadi sarana penting dalam membentuk karakter dan menyampaikan pesan moral kepada generasi muda.